Análise ergonômica do trabalho de catadores de materiais recicláveis - Araújo, Nívia Cecília Kruta de (Universidade Federal de São Carlos, 2017)
With population and industry growth, increased consumption of disposable materials, the activity of the recyclable material collectors has become indispensable to society. The work process of recyclable material collectors involves two steps, the first is the collection of material on the city streets, with the help of bags, cart collection and cooperative trucks and the second is performed at cooperative, sorting and selection of materials collected in the street. This research will consist of three phases, the objectives of which are respectively: Characterize two samples of collectors of recyclable materials regarding the sociodemographic, clinical and psychosocial profile; to verify if there is biomechanical risk and differences in two methods of sorting recyclable materials, one performed on fixed work surface and the other with the aid of conveyor belts, through inclinometry; and to compare the movement of dragging the bag on the floor and to pull the bag with the aid of a cart regarding peak force and muscular electric activity in the dominant upper limb. In the first study, 61 collectors answered the Nordic Musculoskeletal Questionnaire (NMQ); Roland Morris Questionnaire related to low back pain (RMQ); Work Ability Index (WAI); Job Content Questionnaire (JCQ); International Physical Activity Questionnaire (IPAQ); Fagerström Tolerance Questionnaire, which investigates nicotine addiction and the AUDIT questionnaire that investigates alcohol dependence. The second study of the research quantified the postures and velocities of the head, upper back and shoulders adopted by 40 collectors during the sorting process of recyclable materials and analyzed if there was a difference between measurements of two populations of collectors in different sorting processes, one on fixed work surface and another on production line with conveyors belts and the third study of the research consisted of a simulation at the cooperative of recycling, in which the activity of pulling the bag containing recyclable material already selected with and without the aid of a platform cart was compared with the purpose of measuring and comparing the electrical activity of the upper limb muscles and measure the peak of force exerted to pull the bag with a digital dynamometer in 15 collectors. The results of study 1 showed that the collectors studied have the following profile: they are women, young, with low schooling, high consumption of tobacco and alcohol and high turnover in this type of work; report low rates of absenteeism and work-ralated accidents; have good or excellent ability to work; reported to perform a high level of physical activity and present a high prevalence of musculoskeletal disorders and arterial hypertension. The results of study 2 were that, considering the peak of exposure (P90), the means of flexion of the head and upper back and the elevation of the shoulders were, respectively, 40 °, 30 ° and 45 °. In relation to the movements, the velocities identified in P90 were 63.6 ° / s; 55 ° / s and 140 ° / s for the head, upper back and shoulders, respectively. There was a significant difference between the groups for the velocity of movements in all the evaluated regions and percentiles, indicating greater exposure in the fixed work surface. The results of study 3 showed that the use of the cart reduced the force required in the manual material handling, but increased muscle activation. These results indicate that the use of this device may not be advantageous in reducing biomechanical overload.
Keywords: Ergonomia; Catadores de materiais recicláveis; Inclinometria; Eletromiografia; Ergonomics; Collectors of recyclable materials; Inclinometry; Electromyography; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL